INDONESIAN TRADITIONAL MIGRANT WORKER PROFILE CROSS-BORDER KELURAHAN SUNGAI RAYA KECAMATAN MERAL KABUPATEN KARIMUN - Jumiati "; M. Razif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Indonesia is a developing country that is characterized by the development of cities in a fast tempo, this supported with high population growth and labor force. It also increases the demands of various jobs and so on. As experienced by the Karimun lack of jobs and the low level of wages / salary earned make them choose to work as Indonesian workers. Various types of job in other state including construction workers, farm workers, etc. Therefore, the problems in this research are: 1. How Tanjung Balai Karimun Migrant community profile looks like? 2. What are the Karimun factors that causing people work as migrant workers? The purpose of this study is to determine the profile of migrant workers in Karimun as well as to determine the factors that causing Karimun people work as migrant workers. The Subjects of this study are Indonesian Workers who work in Malaysia and Singapore counted 10 people, in which they derived from Kelurahan Sungai Raya. They worked back and forth between the two countries because they only use a traveling passport. The approach used in this study is a qualitative approach, using census techniques, The process of collecting data is by interview, observation and documentation. Being Indonesian Migrant worker is a choice of family economic needs. So their daily needs can be fulfilled.Keyword : Migrant Worker, Traditional Migrant Worker, Profile Cross-Border